2006
DOI: 10.1103/physrevd.74.093012
|View full text |Cite
|
Sign up to set email alerts
|

Precision electroweak constraints on universal extra dimensions revisited

Abstract: We reconsider the constraints on Universal Extra Dimensions (UED) models arising from precision electroweak data. We take into account the subleading contributions from new physics (expressed in terms of the X, Y . . . variables), as well as two loop corrections to the Standard Model ρ parameter. For the case of one extra dimension, we obtain a lower bound on the inverse compactification scale M = R −1 of 600 GeV (at 90% confidence level), with a Higgs mass of 115 GeV. However, in contradiction to recent claim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
114
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 30 publications
3
114
0
Order By: Relevance
“…This finding was later shown to be consistent with observations in the B-physics sector [17] and with the experimental results on anomalous magnetic moments [18,19]. However, in later years, with more data and newer analyses it has been observed that the lower bound on R −1 can surpass the earlier value and can be as high as 700 GeV [27,39,59] at 99% confidence level. Also, similar to R-parity in SUSY scenarios, KK-parity ensures that the lightest n = 1 KK-paricle (the LKP, with odd KK-parity) is an absolutely stable (like the lightest SUSY particle, the LSP) weakly interacting massive particle (WIMP) and is a good dark matter candidate that could provide the right amount of cosmological relic-density [31] 5 .…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…This finding was later shown to be consistent with observations in the B-physics sector [17] and with the experimental results on anomalous magnetic moments [18,19]. However, in later years, with more data and newer analyses it has been observed that the lower bound on R −1 can surpass the earlier value and can be as high as 700 GeV [27,39,59] at 99% confidence level. Also, similar to R-parity in SUSY scenarios, KK-parity ensures that the lightest n = 1 KK-paricle (the LKP, with odd KK-parity) is an absolutely stable (like the lightest SUSY particle, the LSP) weakly interacting massive particle (WIMP) and is a good dark matter candidate that could provide the right amount of cosmological relic-density [31] 5 .…”
Section: Introductionsupporting
confidence: 80%
“…The presence of KK-towers for charged and neutral CP-odd Higgs bosons provides a concrete example of this. The phenomenology of KK-excitations has been studied in great detail in recent times which covers its implications at colliders [3,4,5,6,7,8,9,10,11,12,13,14,15,16], in electroweak/flavour sector via various low-energy observables [17,18,19,20,21,22,23,24,25,26,27,28] and for dark matter/cosmology [5,13,29,30,31,32,33,34,35,36,37,38,39,40] In MUED there are only two extra free parameters when compared to the SM. These are the radius of compactification R (or, alternately R −1 , the scale of compactification) and the cutoff scale Λ of the theory.…”
Section: Introductionmentioning
confidence: 99%
“…1, we see that there are distinctive differences between the SM predictions and those of the UED models, especially the UED6 for N KK ¼ 15, at small values of the [55] ð0:63 À 0:73Þ Â 10 À5 Three-point QCD sum rule [56] ð3:1 AE 0:6Þ Â 10 À5 QCD sum rule [57] ð3:7 AE 0:5Þ Â 10 À5 COQM [58] 0:23 Â 10 À5 Special current [59] ð1:99 þ0:34 À0:31 Þ Â 10 À5 Ioffe current [59] ð0:61 þ0:14 À0:13 Þ Â 10 À6 Pole model [60] ð1:0 À 4:5Þ Â 10 À5 PDG [54] <1:3 Â 10 À3 (CL ¼ 90%Þ compactification factor 1=R. These differences exist in the lower limits obtained by different FCNC transitions in the UED5 and UED6, cosmological constraints, electroweak precision tests [25,29,31,32], and the latest results of the Higgs search at the LHC and of the electroweak precision data for the S and T parameters [34]; however, they become small when 1=R approaches 1 TeV. Our analysis show that the UED scenarios give close results to the SM for 1=R !…”
Section: Decay Width and Branching Ratiomentioning
confidence: 99%
“…It has been shown that in the minimal universal extra dimension (MUED) the KK contributions to the T parameter almost cancel for heavier standard model Higgs [9,15]. However, it was found that in the MUED for Higgs mass heavier than 300 GeV the lightest Kaluza-Klein particle is the charged KK Higgs [16].…”
Section: Massmentioning
confidence: 99%